Design E-School System: A Case of Iraqi School in Kuala Lumpur - Malaysia for Distance Education Purpose - Neama, Ahmed R-H (2010)
As educational technology becomes more prevalent in higher education; teaching is no longer restricted to face-to-face (F2F) instruction. Since Iraqi students who lives outside of Kuala Lumpur are having communications problems with the daily educational curriculum set by the Iraqi school in Malaysia, designing an e-school system prototype for the primary and secondary Iraqi school in Kuala Lumpur- Malaysia is proposed. This research will use Usability Guideline as an aid in designing the system and the research methodology has been used in this study which is Research Design (Vaishnavi & Kuechler, 2004) an agreeable method, excellently chosen, described and accepted among many researchers in information system. The system is developed by using ASP.net (Microsoft Visual Web Developer Express Edition (C#)) programming language environment. The design in this website will increases the efficient interaction and communication between teachers and students and will lead them to obtain better result in education march. Moreover will also become very helpful learning tools where they can show the teachers, check notes, read announcements, download lectures and files.